A Rare Case of Fetal Neural Tube Defect; Iniencephaly Clausus - Arega, Bantayehu Nega; Endalew, Sintayehu Debas; Hailu, Daniel Miskir (American Journal of Perinatology Reports, 2024)
Introduction Iniencephaly is an extremely rare type of neural tube defect characterized by the fusion of the cervical and cervicothoracic vertebrae. This condition results in acute retroflexion of the head, a short neck, significant lordosis of the cervical spine, and an upturned facial appearance. This condition typically results in poor fetal outcomes, with many cases ending in stillbirth or neonatal death.Case summary Here, we present a case of iniencephaly diagnosed during intrapartum ultrasound in a 34-year-old gravida 5 woman referred from a health center to a primary hospital due to preterm premature rupture of membrane and labor. The fetus died intrapartum a few minutes before delivery.Conclusion Iniencephaly remains a rare but critical condition that poses significant challenges for prenatal diagnosis and management. This case underscores the importance of early and accurate imaging in the detection of such severe anomalies, which can provide essential information for clinical decision-making and counseling.
Keywords: iniencephaly clausus; neural tube defect; stillborn